2023
DOI: 10.21203/rs.3.rs-2433963/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of stress control training through podcast on work-life conflict in female residents of Iran University of Medical Sciences 2020-2021

Abstract: Introduction: Given the increasing growth of information in the present age and the growth and development of educational programs and changes that have occurred in the concept of learning, changing the approach to education from traditional methods to e-learning has become important. The present study aimed at investigating the effect of podcast stress control training on work-life conflict in female residents of Iran University of Medical Sciences in 2020–2021. Methods This study was a two-group quasi-expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…For example, reading articles, and blogs, searching online for information about work-related issues, or sharing opinions, quotes, etc., may create a need to balance these activities with time spent outside work. Norouzi et al [ 156 ] examined the effect of stress management training using podcasts on work-life conflict and concluded that stress management through podcasts reduced work-life conflict.…”
Section: Resultsmentioning
confidence: 99%
“…For example, reading articles, and blogs, searching online for information about work-related issues, or sharing opinions, quotes, etc., may create a need to balance these activities with time spent outside work. Norouzi et al [ 156 ] examined the effect of stress management training using podcasts on work-life conflict and concluded that stress management through podcasts reduced work-life conflict.…”
Section: Resultsmentioning
confidence: 99%